Impact on Low Concentration of f-MWCNTs/Fe3O4 Hybrid Filler on Electromagnetic Interference (EMI) Shielding Polymer at X-band - Mazlan, H.I.; Osman, N.H.; Ramli, M.M.; Liew, J.Y.C.; Mazu, N.N.; Majid, M.A.H.M.A.; Reshak, ALI H.; Jeż, B. (Archives of Metallurgy and Materials, 2026)
Preventing electromagnetic interference (EMI) signals from interfering with sensitive electronic devices can help protect it from damage. A lightweight, flexible, and thin EMI shielding polymer provides an alternative to the conventional rigid and heavy metal gasket. In this work, the f-MWCNTs/Fe3O4 hybrid filler was synthesised using the co-precipitation method and used as filler for the EMI shielding polymer. Low-concentration filler of less than 1% was seen as the solution to reduce production costs. Thus, this work used only 0.1 w/v% and 0.5 w/v% of filler concentration of the f-MWCNTs/Fe3O4 hybrid filler. Raman’s spectroscopy study confirmed the presence of carbon and Fe3O4 at 1200 to 1600 cm–1 and 686 cm–1 in the fillers, respectively. Examining the sample’s morphology indicates the filler’s length, diameter, and dispersion throughout the polymer. Electrical properties were studied using impedance spectroscopy, and EMI shielding effectiveness was measured using two-port methods. Results show that shielding polymer with 0.5 w/v% of f-MWCNTs/Fe3O4 hybrid filler results in 3.81×10–5 Scm–1 of electrical conductivity and 5.02 dB total shielding efficiency equivalent to 68.5% EM energy reduction. The total shielding efficiency increased to 8.32 dB (85.34% EM power shield) when the polymer thickness increased to 0.442 mm.